Antiproliferative Activity of Triterpenoid and Steroid Compounds from Ethyl Acetate Extract of Calotropis gigantea Root Bark against P388 Murine Leukemia Cell Lines - Kartini Hasballah; Murniana Sarong; Renzavaldy Rusly; Herdina Fitria; Dewi Rara Maida; Muhammad Iqhrammullah (MDPI AG, 2021)
Calotropis gigantea has been known to produce bioactive secondary metabolites with antiproliferative activities against cancer cells. Herein, we extracted the secondary metabolites using ethyl acetate from its root bark and further tested its antiproliferative activities against P388 murine leukemia cell lines. The subfractions from the ethyl acetate extract was obtained from Vacuum Liquid Column Chromatography (VLCC), and followed by Gravity Column Chromatography (GCC). The subfraction C2 and D1 were identified to contain triterpenoids and steroids with the most potent cytotoxicity against Brine Shrimp Lethality Test (BSLT). A 3-(4,5-dimethylthiazol-2-yl) -2-5 diphenyl tetrazolium bromide (MTT) assay suggested that ethyl acetate extract has the highest antiproliferative activities against P388 murine leukemia cell lines (IC50 = 21.79 μg/mL), as opposed to subfraction C2 (IC50 = 50.64 µg/mL) and subfraction D1 (IC50 = 49.33 µg/mL). The compound identified in subfraction C2 and D1 are taraxerol acetate and calotropone, respectively. Though taraxerol acetate and calotropone were active in inhibiting the leukemic cell lines, their IC50s were lower than the ethyl acetate extract, which is probably due to the synergism of the secondary metabolites.